2017
DOI: 10.1590/s2179-975x4716
|View full text |Cite
|
Sign up to set email alerts
|

Salinity effects on photosynthetic pigments, proline, biomass and nitric oxide in Salvinia auriculata Aubl.

Abstract: Cite as: Gomes, M.A.C. et al. Salinity effects on photosynthetic pigments, proline, biomass and nitric oxide in Salvinia auriculata Aubl. Acta Limnologica Brasiliensia, 2017, vol. 29, e9. Abstract: Aims: Effects of salt stress on the physiology of Salvinia auriculata were investigated. Method: Plants were supplemented with 0, 50, 100 and 150 mmol L -1 NaCl and incubated for 5 days. NO content was evaluated after 2 hours and 5 days. Photosynthetic pigments, proline and nutrients were analyzed after 5 days. Majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 64 publications
2
30
0
1
Order By: Relevance
“…Under stress conditions, the availability of nutrients in the soil is reduced due to a decreased solubility, which leads to decreased absorption and concentrations in plants [54]. The results observed in the present study for nutrient concentrations are parallel to the results obtained by Gomes et al [55], who reported that the Na + , Cl − , and Na/K ratios increased, while Ca 2+ , K + , and Mg 2+ reduced with an increasing salinity; N and P showed no significant differences among saline treatments. Castanares and Bouzo [14] reported that the K concentration decreased and the Na + /K + ratio increased under salinity stress.…”
Section: Discussionsupporting
confidence: 88%
“…Under stress conditions, the availability of nutrients in the soil is reduced due to a decreased solubility, which leads to decreased absorption and concentrations in plants [54]. The results observed in the present study for nutrient concentrations are parallel to the results obtained by Gomes et al [55], who reported that the Na + , Cl − , and Na/K ratios increased, while Ca 2+ , K + , and Mg 2+ reduced with an increasing salinity; N and P showed no significant differences among saline treatments. Castanares and Bouzo [14] reported that the K concentration decreased and the Na + /K + ratio increased under salinity stress.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, stress conditions decreased the NO contents of strawberry plants. Likewise, in Salvinia auriculata, Gomes et al () showed that exposure to high salinity regimes increased extracellular NO level after 2 h, while it decreased when tested after 5 days of salinity stress. Contrarily, in tomato, Manai et al () reported that exogenous application of SNP enhanced salinity stress tolerance which was ascribed to NO‐induced activation of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 96%
“…For example, in different studies, salt-induced enhanced root to shoot ratio has been observed, e.g. in Euonymus japonica (Gómez-Bellot et al 2013), Callistemon citrinus (Álvarez and Sánchez-Blanco 2014) and Myrtus cummunis (Acosta-Motos et al 2015). Astolfi et al (2006) and Zhang et al (2012) have reported that ID stress also enhanced the root to shoot ratio in barley and peanut plants, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations